Extraction of green pigment from Pandanus Odorus - Muhammad Daniel, Selamat (2010)
The objective of this research is to find the best condition to extract green pigment so that it optimize the yield of pigment extract. Pandanus odorus is a typical plant used in everyday cooking in Malaysia. This research project is designated in extracting organic green pigment from Pandanus Odorus or Pandanus Amaryllifolius by using Soxhlet extraction techniques. Chlorophyll were divided into two, chlorophyll a and chlorophyll b, both gives the green color to leaves. The parameters that being studied in this research are the time of extraction, the type of solvents, the size of raw materials and the solvent/raw material ratio. The extract then was separated with the solvents using a vacuum rotary evaporator. The weight of the extract was taken and the extract was diluted with acetone 80% to get the reading of absorbance using UV-Vis to calculate the amount of chlorophyll in the extract. The result shows that the longer time taken for the extract, the smallest size of raw material particle, using high amount of solvent and extract using ethanol 95% will result in the highest yield of green pigment extract.